Color in the home - Helder, Mamie Eva (My University, 1904)
Introduction: By considering the matter of color in the home, we may see that by better development of our knowledge of colors and color harmony, our homes may become places of comfort and beauty, not alone to ourselves but to all who may enter its realms.
Citation: Helder, Mamie Eva. Color in the home. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Color; Home; Home Decoration; Theses